Inhibitory effect of O-propargyllawsone in A549 lung adenocarcinoma cells - Edmilson Willian Propheta dos Santos; Rauan Cruz de Sousa; Mariana Nobre Farias de Franca; Jileno Ferreira Santos; Flaviano Melo Ottoni; Raquel Geralda Isidório; Waldecy de Lucca Junior; Ricardo José Alves; Ricardo Scher; Cristiane Bani Corrêa (BMC, 2023)
Abstract Background Lung cancer is the deadliest type of cancer in the world and the search for compounds that can treat this disease is highly important. Lawsone (2-hydroxy-1,4-naphtoquinone) is a naphthoquinone found in plants from the Lawsone genus that show a high cytotoxic effect in cancer cell lines and its derivatives show an even higher cytotoxic effect. Methods Sulforhodamine B was used to evaluate the cytotoxic activity of compounds on tumor cells. Clonogenic assay was used to analyze the reduction of colonies and wound healing assay to the migratory capacity of A549 cells. Apoptosis and necrosis were analyzed by flow cytometer and Giemsa staining. Hemolysis assay to determine toxicity in human erythrocytes. Results Lawsone derivatives were evaluated and compound 1 (O-propargyllawsone) was the one with the highest cytotoxic effect, with IC50 below 2.5 µM in A549 cells. The compound was able to reduce colony formation and inhibit cell migration. Morphological changes and cytometry analysis show that the compound induces apoptosis and necrosis in A549 cells. Conclusions These results show that O-propargyllawsone show a cytotoxic effect and may induce apoptosis in A549 cells.